Evaluation of Cover Crops and Biopesticides to Manage Meloidogyne incognita on Sweetpotatoes in Greenhouse and Microplot Settings - Schloemer Claire M.; Graham Scott H.; Wang Koon-Hui; Sipes Brent S.; Lawrence Kathy S. (Journal of Nematology)
Interest in organic production is growing, highlighting the need for effective organic integrated management practices for sweetpotatoes. This study aimed to evaluate biopesticides and cover crops for managing Meloidogyne incognita in greenhouse and microplot settings. In the greenhouse, M. incognita reproduction factors were highest following field pea at 15.3 and crimson clover at 5.0, while daikon radish, elbon rye, and cover crop mixes had the lowest factors near 1.0. Summer cover crops sunn hemp, velvetbean, and ‘Piper’ sudangrass did not support M. incognita populations, with reproduction factors below 1. Greenhouse tests revealed similar M. incognita egg numbers/gram of root across all biopesticides, with MeloCon maintaining the lowest numbers. Microplot testing of the biopesticides on sweetpotatoes found M. incognita populations were similar to MeloCon, BotaniGard 22 WP plus Triple Threat Entomopathogenic Nematodes, Chitocide, Seduce, Promax, and Minuet. The highest marketable yield of 0.56 kg/plant was recorded in microplots treated twice with Chitocide, followed by BotaniGard 22 WP plus Triple Threat Entomopathogenic Nematodes, AzaGuard, and Majestene, all of which were comparable to synthetic nematicide, Velum applied at planting. In two field microplot trials, winter cover crops, black oat, daikon radish, and cover crop mixes of all cover crops tested produced the highest sweetpotato yield. Daikon radish, elbon rye, crimson clover, cover crop mix, black oats, and yellow mustard supported lower nematode populations compared to field peas. Overall, all cover crops tested, except field peas and crimson clover, reduced the M. incognita populations during the cover cropping season. Biopesticide MeloCon was most effective in reducing M. incognita populations post sweetpotato planting.